Risk factors for cardiovascular disease in rural South India: cohort study - Prabhdeep Kaur; Sudha Ramachandra Rao; Ramachandran Venkatachalam; Boopathi Kangusamy; Ezhil Radhakrishnan; Kanagasabai Kaliaperumal; Venkatarao Thota; Mohan D Gupte (BMJ Open)
Background and objectives Cardiovascular diseases (CVD) accounted for one-third of the deaths in India. We conducted a cohort study to estimate the incidence of CVD and the association of established risk factors with the incident CVD in a rural population in South India.Design, setting and participants We conducted a community-based cohort study among 6026 adults aged 25–64 years in five villages in Tiruvallur, Tamil Nadu. We did baseline (2005–2007) and two follow-up surveys in 2008–2009 and 2013–2015. Risk factors studied were tobacco, alcohol, hypertension, self-reported diabetes and central obesity.Outcome measures Outcome measures were fatal or non-fatal ischaemic heart disease or cerebrovascular event. We estimated HRs for the risk factors and population attributable fraction (PAF).Results We followed up 5641 (94.4%) subjects, and follow-up duration was 33 371 person years. The overall incidence of cardiovascular event or death was 4.6 per 1000 person years. Current smoking (HR 1.6, 95% CI 1.1 to 2.6) and hypertension (HR 2.2, 95% CI 1.5 to 3.4) were the risk factors among men and accounted for 47% of the PAF. Among women, hypertension (HR 1.8, 95% CI 1.0 to 3.4), self-reported diabetes (HR 4.3, 95% CI 2.2 to 8.1) and central obesity (HR 2.2, 95% CI 1.2 to 4.0) were associated with CVD and accounted for more than half of the PAF.Conclusions We described the high burden of fatal CVD and identified the role of CVD risk factors such as hypertension, self-reported diabetes, smoking and central obesity. There is an urgent need to implement low-cost interventions such as smoking cessation and treat hypertension and diabetes in primary care settings.